2001
DOI: 10.1034/j.1600-0420.2001.079002121.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of glaucoma on the quality of life of patients in Norway

Abstract: ABSTRACT.Purpose: To elucidate the relationship between the visual difficulties reported by patients treated for glaucoma and their objective functional damage, and to evaluate the reliability of the patient responses. Methods: Questionnaires concerning quality of life filled in at home by 589 patients treated for chronic open angle glaucoma were correlated to corresponding questionnaires returned from their ophthalmologists. Results: Few of our patients had a visual field damage judged to be of functional sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 11 publications
2
48
0
4
Order By: Relevance
“…Our study showed that glaucoma patients have different health-related QoL perception than a normal non-glaucomatous population and concurs with the results reported in the literature [3][4][5][6][7][8][9][10][11]. In five out of eight categories of the SF-36 survey, glaucomatous patients scored less than the control group.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our study showed that glaucoma patients have different health-related QoL perception than a normal non-glaucomatous population and concurs with the results reported in the literature [3][4][5][6][7][8][9][10][11]. In five out of eight categories of the SF-36 survey, glaucomatous patients scored less than the control group.…”
Section: Discussionsupporting
confidence: 95%
“…Reports of cross-sectional assessments of QoL in glaucomatous patients in the United States, Sweden, Norway, United Kingdom, Italy and Japan have shown a relative decrease in the functional status and lower healthrelated QoL as compared to non-glaucomatous patients [3][4][5][6][7][8][9][10][11]. The Collaborative Initial Glaucoma Treatment Study is conducting an longitudinal study to assess the health-related QoL implications of glaucoma treatment [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…7 Over the years, several glaucoma-specific patient-reported outcome (PRO) instruments have been developed. [3][4][5][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] While these instruments measure various QOL domains such as activity limitation, symptoms, convenience of eye-drop use, treatment of side effects and satisfaction; each instrument typically measures only one domain. 7,24 For instance, the Glaucoma Quality of Life (GQL-15) measures only activity limitation, 3,25 the Treatment Satisfaction Survey of Intra-ocular Pressure (TSS-IOP) was developed to assess treatment satisfaction and side effects of glaucoma medication, 13 and the Comparison of Ophthalmic Medication for Tolerability (COMTOL) measures tolerability and compliance of glaucoma eyedrops.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies 4,13,14 have reported visual acuity loss and advanced field loss as the main causes associated with lower vQOL in POAG. However, according to Odberg et al, 15,16 QOL impairment occurs much earlier; at the time of diagnosis. We could not do a subgroup analysis based on the staging of the disease as our survey based data did not include the clinical staging of glaucoma.…”
Section: Resultsmentioning
confidence: 99%